Knowledge, Attitudes, and Practices of Hygiene in Hindu Society of Chunikhel, Lalitpur - Bista, Chandra Bhakta (Historical Journal, 2023)
Every religion and culture has its ideas about purity, cleanliness, and what constitutes good physical, personal, and mental cleanliness. The current Hindu society of today stands the same knowledge and customs, but they view hygiene from a different angle. Personal hygiene and sanitation are taken as significant aspects linked to Hindu society. Purity, faith, ritual, and cleanliness in Hindu society are based on the Hindu scriptures related to sanitation and hygiene patterns and the main objective of cleanliness and regular practice in the current society. The study is based on Hindu men and women above 35 years old. The study considers sanitation and hygiene in numerous aspects, including religion, social prestige, self-satisfaction, health, etc. The study includes toilet use, personal hygiene, safe drinking water, and household hygiene as variables. While sanitation and hygiene are prioritized in Hinduism, the modern Hindu community is evolving to recognize not only religious but also physical, social, and psychological well-being. The respondents had high knowledge, favorable attitudes, and good behavior about sanitation and hygiene. Hindu society has internalized and practiced sanitation and hygienic behavior from both religious and health perspectives. The Hindu community also agrees with the new approach to the relationship between Hindu rituals and hygiene and sanitation.